Eksplorasi Kepuasan Pengguna Aplikasi Streaming: Perspektif Pengguna Aplikasi Streaming - Darmayanti, Shalma Darmayanti; Libri, Devita; Hakim, Lukman; Darmayanti, Shalma; Indiarta, Tradiva Yafi’ (Fakultas Ekonomi Universitas Djuanda, 2024)
This study aims to assess user satisfaction with the Bstation application using the PIECES method (Performance, Information, Economy, Control, Efficiency, and Service). Questionnaires were distributed to 50 Bstation users at the Indonesian Education University to see user perceptions of PIECES aspects. The results indicated a strong level of satisfaction with application performance, Performance, Information, Efficiency, and Service. However, improvements are needed in the aspects of Economy and control, where users expect more affordable prices and better control over content preferences. Recommendations include re-evaluating the service's tariff structure, transaction and payment methods, as well as improving security in transactions and consumer data protection. These recommendations are expected to improve user satisfaction of competitive streaming services. ABSTRAK Penelitian bertujuan untuk mengetahui kepuasan pengguna aplikasi Bstation dengan menggunakan metode PIECES (Performance, Information, Economics, Control Efficiency, and Service). Kuesioner disebarkan kepada 50 pengguna Bstation di Universitas Pendidikan Indonesia untuk melihat persepsi pengguna terhadap aspek-aspek PIECES. Hasil penelitian menujukkan tingkat kepuasan yang tinggi pada kinerja aplikasi, yaitu pada aspek Efficiency. Namun, peningkatan diperlukan pada aspek Ekonomi, dalam hal ini pengguna mengharapkan harga yang lebih terjangkau. Rekomendasi yang diberikan meliputi evaluasi ulang terkait struktur tarif layanan, metode transaksi dan pembayaran. Rekomendasi ini diharapkan dapat meningkatkan kepuasan pengguna layanan streaming yang kompetitif.